PERAN KOMISI PEMILIHAN UMUM PROVINSI JAWA TIMUR DALAM SISTEM KONTROL KAMPANYE PADA PEMILIHAN UMUM GUBERNUR JAWA TIMUR 2024 - Muhammad Rangga Diva Ananta Rois’am; Ihsan Dwi Hartanto; Rizkya Dwijayanti (Triwikrama: Jurnal Ilmu Sosial, 2024)
The purpose of this research is to analyze the effectiveness of the implementation of the duties of the General Election Commission ( KPU ) as the organizer of the general elections in accordance with the applicable regulations of Law Number. 7 of 2017 concerning General Elections and various factors that influence them. The type of research used is empirical research conducted at the General Election Commission ( KPU ) of East Java Province.The results of this research conclude that the function of the General Election Commission in creating democratic elections in 2024 is less effective. Even though the level of public participation reached 82%, at the same time invalid ballots reached 8%. There are various factors that influence the effectiveness of the functions of the East Java Province General Election Commission, namely external and internal factors from several locations that are difficult to reach directly and indirectly, quality human resources from General Election Commission of East Java Provincial and public knowledge of elections in general. The recommendation from this research is that the KPU of East Java Provincial should continue to increase synergy between various parties, further improve the quality of human resources, facilities and infrastructure which are still constrained, socialization and voter education so that the General Election Commission of East Java Provincial is able to realize democratic elections. Keywords: Function; General Election Commission Of East Java Provincial; Democratic